The threefold death in Hispania: from Lucanus to "Libro de Buen Amor" - Almagro-Gorbea, Martín (’Ilu. Revista de Ciencias de las Religiones, 2012)
Analysis of two medieval documents on the Celtic rite of the threefold death in Hispania, where hitherto it had been not yet noted. The legend of Santa Marina de Aguas Santas, in Orense, Galicia, is associated with a galaico-lusitanian switch-sauna for initiatic rituals of pre-Roman origin, while the story of the son of the King Alcaraz in the Castillian Libro de Buen Amor (14th century) is a new example of Hispanic Celtic literature, derived from the Arthurian cycle of Merlin, originated in Wales and Brittany, but with some Persian influence.